2021
DOI: 10.1016/j.lfs.2021.119428
|View full text |Cite
|
Sign up to set email alerts
|

Nanotherapeutics in the treatment of acute respiratory distress syndrome

Abstract: Acute respiratory distress syndrome (ARDS) is a form of oxygenation failure primarily characterized by rapid inflammation resulting from a direct pulmonary or indirect systemic insult. ARDS has been a major cause of death in the recent COVID-19 outbreak wherein asymptomatic respiratory tract infection progresses to ARDS from pneumonia have emphasized the need for a reliable therapy for the disease. The disease has a high mortality rate of approximately 30–50%. Despite the high mortality rate, a dearth of effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 207 publications
0
7
0
1
Order By: Relevance
“…Wang et al [ 43 ] also reported that curcumin–SLN administration is more effective than curcumin in attenuating asthma progression. Additionally, other authors have proven that proanthocyanidins–SLNs allow them to play a better role in oxidative stress, suppressing airway epithelial cells [ 44 , 45 ]. Together, these studies indicate the potential of SLNs to improve therapeutic drug efficacy as a drug delivery vehicle.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 43 ] also reported that curcumin–SLN administration is more effective than curcumin in attenuating asthma progression. Additionally, other authors have proven that proanthocyanidins–SLNs allow them to play a better role in oxidative stress, suppressing airway epithelial cells [ 44 , 45 ]. Together, these studies indicate the potential of SLNs to improve therapeutic drug efficacy as a drug delivery vehicle.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a significant progress in nanotechnology, opening a new avenue for improving the efficacy of inhalation therapy of various lung diseases. The nanodrug delivery system has achieved great progress, with the advantages in improving the solubility of drugs, codelivery, targeting delivery of therapeutic drugs, and extending drug half-life for better therapeutic effects. Among various nanocarriers, zeolite imidazolate frameworks-8 (ZIF-8), composed of 2-methylimidazolate and Zn 2+ with minimal cytotoxicity has attracted wide attention . Moreover, ZIF-8 is vulnerable to disintegration in an acid environment, which is advantageous for effective pH-controlled release.…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in critical care, there is currently no effective medication targeting the underlying pathophysiology of ALI, and management of this disease remains supportive, mostly focusing on addressing the inciting cause [ 30 ]. The limited success of pharmacological therapies has led to the development of new agents, such as innovative nanomedicine approaches, specifically aimed at treating ALI [ [31] , [32] , [33] , [34] , [35] ].…”
Section: Introductionmentioning
confidence: 99%